2017
DOI: 10.1111/1744-9987.12570
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen Sensitization in Solid Organ Transplantation: A Primer on Terminology, Testing, and Clinical Significance for the Apheresis Practitioner

Abstract: The human leukocyte antigen (HLA) system is an important immunologic barrier that must be considered for successful solid organ transplantation. Formation of donor-specific HLA antibodies in solid organ transplantation is an important cause of allograft injury and may contribute to recipient morbidity and mortality. Therapeutic plasma exchange is often requested to lower HLA antibody levels prior to or after transplantation and for management of HLA antibodies in the context of organ rejection. In this review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Overall, according to the results obtained in this analysis, it is evident that the most robust sensitized event identified in this group of patients corresponded to a previous kidney transplant, finding that is consistent with previous reports. 16,[19][20][21] Likewise, the main factor related to both detection of IgG subclass and C3d positivity corresponded to the SA MFI. This fact was particularly represented for class II HLA-Abs with a mean MFI for DQ and DR above 10,000 and 7,000, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…Overall, according to the results obtained in this analysis, it is evident that the most robust sensitized event identified in this group of patients corresponded to a previous kidney transplant, finding that is consistent with previous reports. 16,[19][20][21] Likewise, the main factor related to both detection of IgG subclass and C3d positivity corresponded to the SA MFI. This fact was particularly represented for class II HLA-Abs with a mean MFI for DQ and DR above 10,000 and 7,000, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…From the standpoint of HLA sensitization, pregnancy, transfusion and prior transplant are generally considered risk factors [9,10]. Thus, a history of pregnancy, blood transfusion and prior transplant were reviewed.…”
Section: Resultsmentioning
confidence: 99%
“…First, the number of LTX recipients is still in short for analysis. Despite the transplant circumstance changing in Japan, the shortage of organ donors is one of the largest issues in all solid organ transplantation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Analysis was done in sensitized vs non-sensitized recipients, rather than positive vs negative DSA, due to the small sample number.…”
Section: Discussionmentioning
confidence: 99%
“…While there are no routine tests for determining the cellular immune status of the recipient, sensitive methods for detecting HLA antibodies have been developed. The introduction of solid-phase immunoassays has enabled the rapid identification of both complement-and non-complementdependent antibodies by the enzyme-linked immunosorbent assay and flow cytometry (Abbes et al 2017). Thus, HLA antibody testing has become the gold standard for the clinical management of SOT recipients.…”
Section: The Role Of Antibodies In Corneal Graft Rejectionmentioning
confidence: 99%
“…In 1969 it was demonstrated that antibodies directed against MHC antigens are the main cause of rejection in SOT (Patel and Terasaki 1969). HLA sensitization to donor antigens may occur before or after transplantation (Abbes et al 2017;Jordan et al 2004;Taylor et al 2007). The risk factors for anti-HLA antibody production are previous transplantation (50-76% of patients with HLA seroconversion; p < 0.0001), blood transfusion, or pregnancy (Worthington et al 2003).…”
Section: Can Donor-specific Anti-hla Antibodies Contribute To Corneal Graft Rejection?mentioning
confidence: 99%